Strength of steel I-beam to CFT column connection with composite slab - Mulia Orientilize. (2008)
The aim of this project is to investigate the static behavior of composite connections comprising of steel I section beams welded to concrete filled circular hollow section (CHS) column connection with a composite slab subjected to negative bending moment.